2023
DOI: 10.3390/antibiotics12020275
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Management of Skin and Soft Tissue Infections among Surgical Wards in South Africa: Findings and Implications

Abstract: Skin and soft tissue infections (SSTIs) are one of the most common infectious diseases requiring antibiotics. However, complications of SSTIs may lead to the overprescribing of antibiotics and to subsequent antibiotic resistance. Consequently, monitoring the prescribing alignment with the current recommendations from the South African Standard Treatment Guidelines (STG) is necessary in order to improve future care. This study involved reviewing pertinent patients with SSTIs who were prescribed antimicrobials i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 81 publications
2
8
1
Order By: Relevance
“…The majority of patients in our study presented with HIV, hypertension, diabetes and as IV drug users for comorbidities. This mirrors recently published studies in a similar setting in South Africa [34]. This is also similar to the findings of Romano et al ( 2011), who reported an increased prevalence of bone and joint infections in immunocompromised individuals, as well as those with certain lifestyle habits, including intravenous drug use [35].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The majority of patients in our study presented with HIV, hypertension, diabetes and as IV drug users for comorbidities. This mirrors recently published studies in a similar setting in South Africa [34]. This is also similar to the findings of Romano et al ( 2011), who reported an increased prevalence of bone and joint infections in immunocompromised individuals, as well as those with certain lifestyle habits, including intravenous drug use [35].…”
Section: Discussionsupporting
confidence: 91%
“…This could be due to the fact that there is an increase of bone and joint infections due to trauma including traffic accidents and sport injuries in our population, which is more predominant in males as they engage in more risky behaviour [33]. Similarly, a recent study for skin and soft tissue infections in South Africa showed males being more affected [34].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The data collection tool used in our survey was developed from previous studies combined with the considerable experience of the co-authors as well as observing local practices [ 55 , 103 , 110 , 113 , 114 , 139 ]. We have used this method before when developing context-specific data collection forms [ 101 , 131 , 140 , 141 , 142 ].…”
Section: Methodsmentioning
confidence: 99%